Role of comprehensive diabetes care in known diabetes patients from Gujarat state - Sane, Rohit; Mandole, Rahul; Amin, Gurudutt; Ghadigaokar, Pravin; Paranjape, Sneha; Khan, Sadik; Sali, Sanjay; Joshi, Vishwa; Chhatrodiya, Krupa (International Journal of Advances in Medicine, 2020)
Background: Diabetes mellitus (DM) stays as one of the audacious worldwide plagues of the twenty-first century. As per an epidemiological study done in Gujarat, prevalence rate of DM was found to be >8%. CDC therapy is Panchkarma based Ayurvedic therapy for the management of DM. The aim of the present study was to analyze the effectiveness of CDC in patients of DM. Methods: This was a retrospective study conducted at Madhavbaug clinics located in Gujarat, wherein we identified the data of obese patients suffering from type 2 DM (HbA1c ≥6.5%) of either gender and any age. Out of these, data of patients who had been administered CDC with minimum 6 sittings over a span of 12 weeks were considered for the study. Results: Out of 98 patients, number of patients with controlled DM status increased and that with uncontrolled status reduced at week 12, and the mean HbA1c reduced from 8.55 at baseline to 7.15 at week 12 of CDC therapy. Other anthropometric, cardiorespiratory parameters showed statistically significant improvement after 12 week of CDC therapy as compared to baseline, and the consumption of allopathic medications was also significantly reduced. Conclusions: From the findings of the present study, it can be concluded that CDC can serve as effective therapy for management of type 2 DM.